Efektivitas Bakteri Endofit Asal Lahan Basah untuk Menekan Penyakit Hawar Daun Bakteri (Xanthomonas oryzae) pada Padi Beras Merah (Oryza nivara L.): Effectiveness of Endophytic Bacteria from Wetlands to Suppress Bacterial Leaf Blight (Xanthomonas oryzae) in Red Rice (Oryza nivara L.) - Rismawati, Rismawati; Budi, Ismed Setya; ., Mariana (www.ulm.ac.id, 2024)
Brown rice is a type of rice that has many benefits for the health of the body. The main diseases that attack many rice plants and cause a decrease in production include bacterial leaf blight (HDB) caused by the bacterium Xanthomonas oryzae. One alternative to control HDB is to use antagonistic agents, namely endophytic bacteria. This study aims to examine the ability of endophytic bacterial isolates from wetlands and the effect of application time in suppressing the intensity of bacterial leaf blight and to determine its effect on the growth of brown rice plants. There were 2 isolates of endophytic bacteria tested in this study, namely isolates of root origin (AKL) and isolates of stem origin (BLR) isolated from karamunting plants. This study used a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The treatment used in this study was only the pathogen Xanthomonas Oryzae (control), soaking seeds with endophytic bacteria from roots, soaking seeds with endophytic bacteria from stems, soaking seeds + application when transplanting with endophytic bacteria from roots and seed soaking + application when transplanting Plant with stem-origin endophytic bacteria. Treatment of endophytic bacteria on brown rice seeds and application during transplanting was able to reduce the intensity of bacterial leaf blight (X. oryzae) with a disease intensity of 83% and an effectiveness of 15.6%. Treatment of endophytic bacteria on rice seeds did not inhibit seed germination and was able to increase the number of tillers, but had not been able to affect the increase in plant height.